From Thanos to Arya Stark: Influence of Meme War in Indian Lok Sabha Election 2019 - Pandey, Neha (Journal of Advanced Research in Journalism & Mass Communication, 2022)
In the 2019 Lok Sabha Elections, one of the largest celebration of Indian democracy, political parties and candidates put forth content on various social media channels throughout the election process. When Modi dominated the debate during the 2014 Lok Sabha election, social media sprang onto the forefront. This time, however, his competitors look to be catching up. No party fell behind in interacting via social media or conducting political advertising. According to Google and Facebook data, 27 crores was spent on social media advertising. Media consumers were creating tens of thousands of fan sites and profiles. Numerous forms of content circulated over social media. Memes, the newest form of political speech, was among them. Throughout the whole election campaign period, up until the date of the poll results, social media was swamped with humorous memes. All were exploited to create memes on social media, from Avengers: Endgame and Game of Thrones characters and events to Bollywood movies and actors-actresses. An exploratory study employing content analysis and survey techniques as research methods is conducted to investigate how much value users place on memes and identify the various types of memes circulated during the election. An advanced Twitter search engine utilizing the hashtag #Lok SabhaElections2019 was used to extract a sample of 108 memes made on the microblogging site Twitter. The electoral commission of India provided the hashtag. In addition, a survey of media consumers and journalists was done using a standardized questionnaire. This outcome led us to the significant conclusion that there is no conclusive proof that memes directly influence voters’ political decisions.